Microglial ApoD‐induced NLRC4 inflammasome activation promotes Alzheimer's disease progression - Yaliang Yu; Jianzhou Lv; Dan Ma; Ya Han; Yaheng Zhang; Shanlong Wang; Zhitao Wang (Animal Models and Experimental Medicine)
Abstract Background Alzheimer's disease (AD) is a progressive neurodegenerative disease with no effective therapies. It is well known that chronic neuroinflammation plays a critical role in the onset and progression of AD. Well‐balanced neuronal‐microglial interactions are essential for brain functions. However, determining the role of microglia—the primary immune cells in the brain—in neuroinflammation in AD and the associated molecular basis has been challenging. Methods Inflammatory factors in the sera of AD patients were detected and their association with microglia activation was analyzed. The mechanism for microglial inflammation was investigated. IL6 and TNF‐α were found to be significantly increased in the AD stage. Results Our analysis revealed that microglia were extensively activated in AD cerebra, releasing sufficient amounts of cytokines to impair the neural stem cells (NSCs) function. Moreover, the ApoD‐induced NLRC4 inflammasome was activated in microglia, which gave rise to the proinflammatory phenotype. Targeting the microglial ApoD promoted NSC self‐renewal and inhibited neuron apoptosis. These findings demonstrate the critical role of ApoD in microglial inflammasome activation, and for the first time reveal that microglia‐induced inflammation suppresses neuronal proliferation. Conclusion Our studies establish the cellular basis for microglia activation in AD progression and shed light on cellular interactions important for AD treatment.